490. A Randomized Crossover Study to Evaluate Interventions to Reduce Contamination during Reuse of N95 Respirators. (31st December 2020) - Li, Daniel; Alhmidi, Heba; Pearlmutter, Basya; Cadnum, Jennifer; Wilson, Brigid; Donskey, Curtis
Abstract: Background: During the Coronavirus Disease 2019 pandemic, shortages of personal protective equipment (PPE) have forced many healthcare facilities to require personnel to reuse N95 respirators. We hypothesized that use of correct technique such as changing gloves after N95 contact or providing rapid decontamination between each use would reduce the risk for contamination. Methods: We conducted a randomized crossover study using simulated patient care interactions to compare the effectiveness of interventions to reduce contamination of personnel and the environment with high-level N95 contamination (10 7 plaque-forming units [PFU] of bacteriophage MS2 applied to front of respirator). Ten healthcare personnel performed 4 randomly-assigned standardized examinations of mannequins including: 1) Control (PPE donning and doffing not including glove change after N95 contact); 2) Glove change after any N95 contact; 3) Control with 1-minute ultraviolet-C light (UV-C) treatment between simulations; 4) Control with 30-second steam treatment between simulations. A second trial was conducted with groups 1–3 using a lower inoculum (10 5 PFU). The frequencies of participant and environmental contamination were compared. Results: As shown in Figure 1.A, use of a highly contaminated N95 respirator resulted in frequent MS2 contamination in the Control, Glove change, and UV-C groups, but was dramatically reduced with steam treatment of the N95. With the lower level of contamination, MS2 contamination occurred less frequently across all groups, and was significantly reduced in the UV group, compared to the Control (Figure 1.B). Figure 1: Bacteriophage MS2 contamination during simulated patient care interactions with contaminated N95 respirators Conclusion: Reuse of contaminated N95 respirators resulted in contamination of personnel and the environment even when correct technique was used. Rapid decontamination technologies can reduce the risk for transmission. Disclosures: All Authors : No reported disclosures